Southeast Research and Extension Center Agricultural Research 2021 (Kansas Agricultural Experiment Station Research Reports, 2021)
Report of agricultural research from Southeast Research and Extension Center, Kansas State University.
Keywords: beef cattle; forage; cropping systems